The Influence of Supportive Coworkers, Appropriate Rewards, and Supportive Work Environment Conditions on Job Satisfaction at the Head Office of PT Pelindo Multi Terminal Belawan - Ela Diovera Niel; Emi Wakhyuni; Samrin Samrin (Journal of Management, Economic, and Accounting, 2026)
This study aimed to analyze the influence of supportive coworkers, appropriate rewards, and supportive work environment conditions on employee job satisfaction at the Head Office of PT Pelindo Multi Terminal Belawan. The research employed an associative-quantitative approach with a multiple linear regression method. The population consisted of all 209 employees, while the sample included 68 permanent employees who were selected using the Slovin formula and determined through purposive sampling techniques. Data collection was carried out through the distribution of questionnaires in 2025, and the entire analytical process was processed using SPSS 24.0 software. The results showed that supportive coworkers, appropriate rewards, and supportive work environment conditions had a positive and significant influence both partially and simultaneously on employee job satisfaction. The findings also indicated that the appropriate rewards variable was the most dominant factor affecting job satisfaction compared with the other variables. Approximately 85.7% of job satisfaction was explained by the three variables, namely coworkers, rewards, and work environment, with a very strong relationship. These results suggested that perceptions of reward fairness, clarity of reward processes, and recognition of individual contributions had the greatest influence on employees’ evaluations of their work. This study provided empirical contributions to human resource management studies, particularly those related to job satisfaction in the port service industry.